Analisis Hambatan Belajar Siswa Kelas Tinggi UPTD SDN Kraton 1 Bangkalan dalam Mencapai Prestasi Optimal - Adisti Istivari Wahyudi; Saniyatus Safaah; Arnetta Amelia Putri; Nilamsari Damayanti Fajrin; Erna Dwi Lestari (Lembaga Yasin AlSys, 2025)
The learning process in schools does not always proceed smoothly, as students often encounter difficulties in understanding subject matter, particularly in Mathematics and English. These challenges negatively impact students' academic performance and hinder the achievement of learning objectives. This study aims to describe teachers’ efforts in addressing learning difficulties in Mathematics and English, the use of instructional media, and the obstacles encountered during the learning process. A descriptive qualitative method was used, with research subjects consisting of teachers and upper-grade students at UPTD SDN Kraton 1 Bangkalan. Data were collected through observation, interviews, and documentation. The results show that teachers strive to enhance students’ interest and comprehension by utilizing engaging and relevant learning media and conducting remedial sessions for students scoring below the Minimum Mastery Criteria (KKM). However, several challenges were identified, including limited availability of media, mismatches between media and students’ needs, and underutilization of available resources. Additionally, two students were found to experience learning difficulties with differing characteristics. The study concludes that creative and innovative instructional strategies through the effective use of learning media are essential for addressing student learning difficulties and supporting the successful achievement of learning objectives, particularly in Mathematics and English subjects.